The Impact Of Entrepreneurship In Achieving The Economic Dimension A Benchmark Study - Assisse, Sara; Khenafer ,Ali (جامعة الوادي University of Eloued, 2025)
This study addressed the impact of entrepreneurship on achieving the economic dimension, referred to as economic growth. Time series were used as a method for analytical review, applied to a sample of the studied countries. The study highlighted the concept of entrepreneurship, its dimensions, and its importance, as well as the definition of economic growth, its measures, and the impact of entrepreneurship on achieving economic growth. The study concluded with recommendations to strengthen innovation as a key driver of economic growth and to provide government support and dedicated funding for research and development to encourage it.
The impact of entrepreneurship in achieving the economic dimension A benchmark study for the period 2016-2022 in the countries (Saudi Arabia, UAE, Qatar)
مقال
Keywords: Entrepreneurship; Economic Growth; Innovation; Entrepreneurship Activity